Hubungan Tingkat Stress dan Perilaku Konsumsi Makanan Cepat Saji terhadap Kejadian Dismenore pada Remaja Putri di Kelas X SMA Anwarul Hidayah - Mahdalena, Mahdalena; Hardianti, Iis Sri (Universitas Malahayati, 2025)
ABSTRACT Dysmenorrhea is a pain that generally occurs during menstruation due to contractions of the uterine muscles due to an imbalance of prostaglandin hormones. Dysmenorrhea is experienced by many women in the world with more than 50% of women in every country known to have dysmenorrhea. In Indonesian society, especially among teenagers, fast food has become a habit and part of the lifestyle. Adolescence is prone to stress due to many changes such as physical, psychological, hormonal and social changes. Based on the above, the researcher is interested in conducting a study entitled